2021
DOI: 10.5551/jat.58248
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Kynurenine Pathway Enzymes in Aortic Atherosclerotic Aneurysm: Macrophage Kynureninase Downregulates Inflammation

Abstract: Aims: Inflammation and hypertension contribute to the progression of atherosclerotic aneurysm in the aorta. Vascular cell metabolism is regarded to modulate atherogenesis, but the metabolic alterations that occur in atherosclerotic aneurysm remain unknown. The present study aimed to identify metabolic pathways and metabolites in aneurysmal walls and examine their roles in atherogenesis. Methods: Gene expression using microarray and metabolite levels in the early atherosclerot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Consistently, reduced kynurenine production was shown to be associated with an increased inflammatory response in the lungs of aged individuals during an influenza infection [ 201 ]. Another study found kynurenine metabolism pathways were upregulated in the inflammatory disease, aortic atherosclerotic aneurysm, and the metabolism of kynurenines help downregulate inflammation [ 202 ]. With progression of the kynurenine metabolism pathways, tryptophan is ultimately broken down into small molecules such as NAD + , picolinic acid (PA), ATP, and CO 2 [ 72 ], which each having different roles in the anti-inflammatory function of macrophages.…”
Section: Amino Acid Metabolism In Myeloid Cellsmentioning
confidence: 99%
“…Consistently, reduced kynurenine production was shown to be associated with an increased inflammatory response in the lungs of aged individuals during an influenza infection [ 201 ]. Another study found kynurenine metabolism pathways were upregulated in the inflammatory disease, aortic atherosclerotic aneurysm, and the metabolism of kynurenines help downregulate inflammation [ 202 ]. With progression of the kynurenine metabolism pathways, tryptophan is ultimately broken down into small molecules such as NAD + , picolinic acid (PA), ATP, and CO 2 [ 72 ], which each having different roles in the anti-inflammatory function of macrophages.…”
Section: Amino Acid Metabolism In Myeloid Cellsmentioning
confidence: 99%
“…150 Similarly, kynureninase and KMO were upregulated in macrophages of aortic atherosclerotic aneurysm in patients who underwent aortic surgery. 152 Furthermore, 3-hydroxyanthranilic acid, in an NF-kB-dependent manner, increases the expression of matrix metalloproteinase 2 in VSMCs and accelerates the formation and exacerbation of Ang II-mediated abdominal aorta aneurysm in both Apoe −/− and Apoe −/− /IDO −/− mice. 150 Moreover, kynureninase knockdown strongly decreased 3-hydroxyanthranilic acid and matrix metalloproteinase 2 and partly prevented Ang II-mediated abdominal aorta aneurysm in mice.…”
Section: Kynurenine Pathway and Aneurysmmentioning
confidence: 99%
“…In one study, silencing kynureninase, which was upregulated in macrophages in the aneurysmal walls in patient suffering from AAA, increased the expression of IL-6 and IDO in cultured macrophages, suggesting an anti-inflammatory effect of macrophage kynureninase [ 95 ]. In contrast to this study, another finding highlighted a role of the KP catabolite, 3-OHKyn, on EC apoptosis and dysfunction through the generation of superoxide anions by nicotinamide adenine dinucleotide phosphate (NAD(P)H) oxidase [ 96 ].…”
Section: Trp Catabolism In Cardiometabolic Diseasesmentioning
confidence: 99%